A Vedic Approach to Environmental Injustice: An Exploration into the Nature of the Ganga and Interconnected Consciousness - CARLY CORRITORE (Dr. Chinmay Pandya, 2015)
Nature has traditionally been a vital complement of human life in Indian tradition. The sacred river Ganges holds deep spiritual and mythological symbolism and has earned the reverence and worship of Indians for centuries.  Now there is a mentality developing in India in which new hierarchies of values are being created and traditional teachings and core ethics are compromised.  The current scenario in India speaks of a disconnection from ancient intrinsic values of the interconnected roles of humans and nature. By using the Ganges as a case study this study will explore the shift and renewal of the spiritual essence of the interconnection. In an attempt to understand the shift of values, this study will examine the human-nature relationship given in Vedic philosophy and core values and ethics existing in this interconnectedness.  The study will investigate how and why the relationship between human beings and nature has changed, what ethics and values have been undermined, and how the ethics necessary for coexistence can be rediscovered and renewed today.